Sensory characteristics of ice cream produced in the United States and Italy - Thompson, Kelly R.; Chambers, Delores H.; Chambers, Edgar, IV (My University, 2009)
This study was conducted to define and compare sensory characteristics of high quality Italian gelati to ice creams produced in the United States. Trained descriptive sensory panelists evaluated gelato samples in Italy, purchased direct from local gelaterias, and ice cream samples in the U.S., purchased from grocery stores and local shops. In general, gelati obtained higher overall fruity and fruit ID scores, chocolate gelati higher chocolate and cocoa notes, and vanilla gelati higher vanilla and lower vanillin intensities than most U.S. ice creams. Gelati were consistently associated with higher density, lower firmness, and slower meltdown. When compared to U.S. ice creams, Italian gelati are characterized by specific sensory properties: “true to type” flavors: high intensity flavors considered to be typical to that flavor category or specific fruit and are combined with a dense, smooth texture that allows for the development of flavor, body and bloom, enhancing the perception of flavors.
Keywords: Sensory; Ice cream; Gelato; Descriptive analysis; Flavor; Amplitude; United States; Italy